2008
DOI: 10.1103/physrevlett.100.113401
|View full text |Cite
|
Sign up to set email alerts
|

Melting of Trapped Few-Particle Systems

Abstract: In small confined systems predictions for the melting point strongly depend on the choice of quantity and on the way it is computed, even yielding divergent and ambiguous results. We present a very simple quantity that allows us to control these problems-the variance of the block averaged interparticle distance fluctuations.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 16 publications
5
56
0
Order By: Relevance
“…60,61 To emphasize the role of the coupling strength and the packing fraction onto the particle uctuations, we calculate the relative IDF via the denition used in ref. 61 and 62…”
Section: Inter-particle Distance Fluctuationsmentioning
confidence: 99%
“…60,61 To emphasize the role of the coupling strength and the packing fraction onto the particle uctuations, we calculate the relative IDF via the denition used in ref. 61 and 62…”
Section: Inter-particle Distance Fluctuationsmentioning
confidence: 99%
“…We mention that, for very small systems, recently a more appropriate quantity has been proposed: the variance of the block-averaged interparticle distance fluctuations, see Ref. 40.…”
Section: Conditions For Crystal Formationmentioning
confidence: 99%
“…A rather detailed analysis of melting in Coulomb balls was performed by APOLINARIO [100] who observed that the melting often proceeds in several steps. Finally, in a recent study [120] it was observed that the quantity u rel has a number of difficulties in small systems -the result strongly depends on the way of calculation. Instead it was suggested to use another quantity -the variance of the block averaged interparticle distance fluctuations (VIDF)…”
Section: Finite Temperature Effects Solid-liquid Phase Transitionmentioning
confidence: 99%